292 Patient Centred Care in the Outpatient Department. (28th February 2022) - Moore, E.; Dholoo, F.; Dinneen, A.; Solan, M.
Abstract: Aim: The NHS long term care plan recognises the need for a personalised approach to healthcare. Patient initiated follow up (PIFU) is one way in which the NHS can support patients with becoming more autonomous in decisions about their own health. Method: Our trust implements PIFU in 2 ways. Firstly, patients considering an elective operation were provided with a clinic letter detailing the treatment options and a PIFU card. They were discharged and asked to return the card if they wished to proceed to surgery, at which point they were added to the waiting list. Secondly, patients discharged from clinic were provided with a card which they returned if they needed to be seen again for the same complaint. Results: 95 patients were recruited for the operative pathway. 38 (40%) requested surgical treatment within 6 months. 149 patients were recruited for the clinic pathway, of which 17% returned for the same condition within 6 months. Conclusions: This study has shown that 60% of patients choose, after meaningful dialogue and time to reflect, to avoid surgical treatment. In all cases the surgeon would have "added to the waiting list" had a joint decision been made at the end of the consultation. Furthermore, 83% of patients who would ordinarily have had a routine follow-up appointment did not return to clinic. This PIFU system empowers patients to make decisions about treatment. Offering direct access to the operative waiting lists and clinics has multiple benefits: fewer primary care and hospital appointments; reduced waiting times and reduced costs.